Media Used by English Teachers in Teaching Listening at Junior High School in Payakumbuh District - Roza Susanti; Dwi Settya Mahaputri (Institut Darul Quran Payakumbuh, 2023)
Listening is the activity of obtaining information about processes by listening to sounds. This study is a descriptive study using qualitative methods. The aim was to identify the media used by English teachers in listening classes at secondary schools in Payakumbuh district. Researchers conducted this study at a secondary school in Payakumbuh District. Twelve English teachers from Payakumbu District Middle School were selected through an open recruitment process. Researchers used questionnaires and interviews to obtain data. After conducting the study, the findings revealed that graphic media, which received percentages of 54.4% with a final score of 604, made up the majority of the materials used by English teachers to teach listening. Then, audio media received percentages of 25.4% and a score of 283. Audiovisual media, which is hardly often used, received percentages of 20.2% with a final score of 224. According to the data from the questionnaire and the teachers' responses from the interview, English teachers also employ graphic, audio, and audio visual media to teach listening. Thus, it can be said that listening skills were taught using media by English teachers at Payakumbuh District Junior High School.